2017
DOI: 10.1002/slct.201601561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N‐Doped Graphene for Properties of Pt/N‐Doped Graphene Catalyst

Abstract: Nitrogen doping into graphene was carried out by heating Graphene Nano Sheets (GNS) in ammonia to produce N‐doped graphene (N−G). The N−G was used as a support material for Pt catalyst as well as a catalyst itself for half‐cell cathode reaction of hydrogen fuel cell (H2FC). It is found that the Oxygen Reduction Reaction (ORR) electro catalytic activity for N−G 900 (0.63 V versus RHE) is higher than GNS. It indicates that the incorporation of nitrogen in N−G may affect the ORR activities. XPS results exhibit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Previous studies have clearly shown that doping of nitrogen can influent π–d hybridization in terms of electronic structures. [ 36 ] Figure S4 (Supporting Information) shows CV measurements of Pt‐N‐rGO, Ni‐N‐rGO, and PtNi‐N‐rGO. The PtNi‐N‐rGO represents much higher peak current.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have clearly shown that doping of nitrogen can influent π–d hybridization in terms of electronic structures. [ 36 ] Figure S4 (Supporting Information) shows CV measurements of Pt‐N‐rGO, Ni‐N‐rGO, and PtNi‐N‐rGO. The PtNi‐N‐rGO represents much higher peak current.…”
Section: Resultsmentioning
confidence: 99%
“…40 Then, it was reduced tobe graphene nanosheets. 41,42 The 30 wt% Pt catalysts were deposited onto GNS using a platinum (Pt) precursor of [H 2 PtCl 6 .6H 2 O] (Alfa Aesar, A Johnson Matthey Company). Briefly, the ethanol solution of the precursor was mixed with the ethanol solution of GNS.…”
Section: Methodsmentioning
confidence: 99%
“…That is caused N atoms incorporate with carbon atoms. It is possible because N may donate its electrons to the π-graphene system 52 .…”
Section: Sem-edx Analysismentioning
confidence: 99%